A novel antibody targeting sequence 31–35 in amyloid β protein attenuates Alzheimer's disease‐related neuronal damage. Issue 2 (8th November 2016) - Cheng, Li; Zhang, Jun; Li, Xin‐Yi; Yuan, Li; Pan, Yan‐Fang; Chen, Xiao‐Rong; Gao, Tian‐Ming; Qiao, Jian‐Tian; Qi, Jin‐Shun
ABSTRACT: Amyloid β protein (Aβ) plays a critical role in pathogenesis of Alzheimer's disease (AD). Our previous studies indicated that the sequence 31–35 in Aβ molecule is an effective active center responsible for Aβ neurotoxicity in vivo and in vitro . In the present study, we prepared a novel antibody specifically targeting the sequence 31–35 of amyloid β protein, and investigated the neuroprotection of the anti‐Aβ31–35 antibody against Aβ1–42 ‐induced impairments in neuronal viability, spatial memory, and hippocampal synaptic plasticity in rats. The results showed that the anti‐Aβ31–35 antibody almost equally bound to both Aβ31–35 and Aβ1–42, and pretreatment with the antibody dose‐dependently prevented Aβ1–42 ‐induced cytotoxicity on cultured primary cortical neurons. In behavioral study, intracerebroventricular (i.c.v.) injection of anti‐Aβ31–35 antibody efficiently attenuated Aβ1–42 ‐induced impairments in spatial learning and memory of rats. In vivo electrophysiological experiments further indicated that Aβ1–42 ‐induced suppression of hippocampal synaptic plasticity was effectively reversed by the antibody. These results demonstrated that the sequence 31–35 of Aβ may be a new therapeutic target, and the anti‐Aβ31–35 antibody could be a novel immunotheraputic approach for the treatment of AD. © 2016 Wiley Periodicals, Inc.